2011
DOI: 10.2478/v10033-011-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exchange Rate Volatility on Turkish Exports: 1993-2009

Abstract: This paper attempts to investigate the long-run and short-run relationships between Turkish exports, exchange rate volatility, foreign income, and relative prices by employing quarterly data for the period 1993Q3-2009Q4. Towards this purpose, multivariate cointegration and error correction model (ECM) techniques are used in this study. The long-run estimation results suggest that foreign income and real exchange rate volatility exert positive and statistically significant impacts on Turkish exports, while rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The positive impact of volatility on exports is confirmed by A. Kasman and Kasman (2005), Ozturk and Kalyoncu (2009), Altintaş et al (2011), Nazlioglu (2012), Erdal et al, (2012), Cetin and Karakaya (2013) and Kilic and Yildirim (2015). One might argue that although volatility in the exchange comprises some risk it might provide the businesses with opportunities to reach greater profits (Grauwe, 1992; 1998; Van, 2011).…”
Section: The Theoretical and Empirical Facts Underpinning The Estimation Outputmentioning
confidence: 79%
See 2 more Smart Citations
“…The positive impact of volatility on exports is confirmed by A. Kasman and Kasman (2005), Ozturk and Kalyoncu (2009), Altintaş et al (2011), Nazlioglu (2012), Erdal et al, (2012), Cetin and Karakaya (2013) and Kilic and Yildirim (2015). One might argue that although volatility in the exchange comprises some risk it might provide the businesses with opportunities to reach greater profits (Grauwe, 1992; 1998; Van, 2011).…”
Section: The Theoretical and Empirical Facts Underpinning The Estimation Outputmentioning
confidence: 79%
“…For the time interval of 1980–2005, Ozturk and Kalyoncu (2009) find that the volatility has positive effect on Turkey’s export by conducting residual-based cointegration estimations. Altintaş et al (2011) searches the effect of real exchange rate volatility on aggregate Turkish exports during the period 1993–2009 by considering the ARDL cointegration technique and error correction model. According to their long-run estimation evidence, the real exchange rate volatility has a positive and statistically significant impact on Turkish exports.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicated that fluctuations in the exchange rate had a negative impact on non-oil exports (29). Moreover, investigating the effects of exchange rate fluctuations on the exports of some Asian countries showed that the fluctuations in the exchange rate had negative effects on the exports of the investigated countries (30)(31)(32)(33). However in some other countries, the exchange rate is just a variable and in these countries, exports depend on factors such as specialty, high technology, and marketing; therefore, after investigating the supply and demand, it will become possible to recognize the results of exchange rate fluctuations in a country's economic realm.…”
Section: Discussionmentioning
confidence: 99%
“…Because the exchange rate volatility has an immense spillover effects throughout the various macroeconomic indicators. Some researchers argue that the volatility of exchange rates would have an adverse effect on trade flows; the others argue that the volatility of exchange rates would encourage trade flows (Altintaş et al, 2011). Many prominent economists believe that undervaluation promotes growth because it motivates firms to invest in high productivity tradable industries, which increases overall productivity rates (Rodrik, 2008).…”
Section: Introductionmentioning
confidence: 99%